Influence of Cultural Intelligence and Psychological Capital on Service Quality: A Study of the Hotel Industry in Sabah, Malaysia - Mary Monica Jiony; Lew, Tek Yew; Daria Gom; Geoffrey Harvey Tanakinjal; Stephen Sondoh Jr (MDPI, 2021)
Cultural intelligence (CQ) and psychological capital (PsyCap) are two critical characteristics that can be leveraged to develop dynamic hotel frontline employees capable of sustaining service excellence. While both the hotel industry and researchers have followed this trend, there are few studies in the research setting that delve into this relationship. This study examines the effects of cultural intelligence on service quality with psychological capital serving as a mediating variable. To confirm the proposed hypotheses, this study collects 300 questionnaires from four- and five-star hotels. For quantitative analysis, partial least squares structural equation modelling was used. The findings revealed that PsyCap is favorably associated with three components of CQ (metacognitive, motivational, and behavioral elements). Simultaneously, the CQ cognitive and behavioral elements were found to be positively related with service quality (SQ). These findings offer hotel managers practical guidance on how to evaluate critical internal resources and capabilities as a source to implementing and sustaining human resource practices.